Literature Review; Stabilitas Tanda-tanda Vital Neonatus Segera Mandi dengan Tunda Mandi - Fransiska Ompusunggu; Yeni Rustina (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction: Bathing of neonate is a part of the birth process by cleaning the baby's body, watering or soaking. However, neonates may experience heat loss more rapidly and show signs of vital instability. Objectives: The purpose of this study was to compare the stability of the vital signs of neonates who immediately took a bath and who delayed bathing. Methods: the research method as a comprehensive search strategy, namely articles in the database of research journals through the Scopus database, Proquest, Clinical Key, and Science Direct with full text criteria and published in years. 2016-2020. Results: The results obtained in this study indicate that it is advisable to delayed bathing in newborns so that the stability of vital signs is better